1986
DOI: 10.1111/j.1600-0404.1986.tb04639.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin abnormalities in patients with myotonic dystrophy

Abstract: In order to further investigate immunoglobulin (Ig) abnormalities in patients with myotonic dystrophy (MyD), we examined 65 patients with MyD for their serum concentration of IgG in relation to their immunological functions as well as other clinical and laboratory findings. Turnover of IgG was also examined. We found significant and selective reduction of serum IgG in patients with MyD. The serum concentration of IgG in patients with MyD had a significant negative correlation with duration of illness, which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Cases include autoimmune mediated hyperthyroidism, Addison’s disease, Hashimoto’s thyroiditis, thrombocytopenic idiopathic purpura and myasthenia gravis. Also, hypogammaglobulinaemia and increased frequency of autoantibody formation has been described in DM1 patients 14 15 16 17 18 19 20. To date, no cohort study has confirmed these sporadic observations and no mechanism of action has been elucidated conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Cases include autoimmune mediated hyperthyroidism, Addison’s disease, Hashimoto’s thyroiditis, thrombocytopenic idiopathic purpura and myasthenia gravis. Also, hypogammaglobulinaemia and increased frequency of autoantibody formation has been described in DM1 patients 14 15 16 17 18 19 20. To date, no cohort study has confirmed these sporadic observations and no mechanism of action has been elucidated conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…One report described significant, selective reduction of serum concentrations of immunoglobulin (Ig)G in MD1 patients. [8] In this case, the normal serum IgG level of 1511 mg/dL might not have been associated with MD1.…”
Section: Discussionmentioning
confidence: 86%
“…Other work has found a longer duration of DM1 is associated with lower serum IgG levels, both in cross-sectional analysis and in longitudinal study of individual patients with DM1 over time [7]. Suzumura et al found no differences in broad lymphocyte populations or mitogen-driven proliferation [7], nor any differences in in vitro production of IgG between patients with DM1 and healthy controls. Bone marrow cellularity and plasma cell counts were also comparable [7].…”
Section: Discussionmentioning
confidence: 99%
“…Suzumura et al found no differences in broad lymphocyte populations or mitogen-driven proliferation [7], nor any differences in in vitro production of IgG between patients with DM1 and healthy controls. Bone marrow cellularity and plasma cell counts were also comparable [7]. Injection of radiolabeled 125 -I-IgG led to more rapid clearance of the 125 -I-IgG from day 2–4 in six patients with DM1 compared with seven healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation